Adolescents' Perceptions of Early Marriage in Setupatok Village, Mundu District - Ani Nurhaeni; Dea Andini; Lily Wahyuni; Yani Kamasturyani (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Early marriage is a marriage carried out by individuals under the age of 19. This phenomenon is still a serious problem in Setupatok Village, Mundu District. Adolescent perceptions of early marriage are one of the factors that can influence the decision to marry at a young age. This study aims to determine the relationship between adolescent perceptions and the incidence of early marriage in Setupatok Village, Mundu District. Method: The research method used is quantitative with a cross-sectional research design. The research sample was 82 respondents selected using the proportional random sampling technique. Data were collected through questionnaires and analyzed using the chi-square statistical test. Result: The results showed that 67 adolescents (81.7%) had a good perception of early marriage, while 15 adolescents (18.3%) had a bad perception. The incidence of early marriage in Setupatok Village was recorded as 64 adolescents (78.0%) had married at an early age, while 18 adolescents (22.0%) were not married. Statistical tests showed a significant relationship between adolescent perceptions and the incidence of early marriage (p-value = 0.000; p <0.05). Conclusion: The results of this study are expected to contribute to efforts to prevent early marriage by increasing adolescent awareness of the impact of marriage at a young age. Reproductive health education and counseling are strategic steps in changing adolescent perceptions of early marriage.